Present-Day Sea Level Variations in Coastal Areas from Daily to Multidecadal Time Scales: Observations and Causes - A. Cazenave; R. Almar; P. Almeida; N. K. Ayoub; J. H. Bettencourt; F. Birol; W. Han; M. Herrmann; S. Jevrejeva; L. Leclercq; F. Niño; J. Oelsmann; et al. (Surveys in Geophysics, 2026)

The carbon dioxide radical anion as a reductant in water treatment and atmospheric chemistry: a review - Thomas Schaefer; Jonathan D. Raff; Mallikarjuna N. Nadagouda; Eric Lichtfouse; Dan Meyerstein; Hartmut Herrmann; Virender K. Sharma (Environmental Chemistry Letters, 2026)
The carbon dioxide radical anion, CO 2 ●− , is a highly reactive radical species involved in the reduction of the CO 2 greenhouse gas, organic synthesis, atmospheric aerosol chemistry, and treatment of halogenated compounds. In recent years, CO 2 ●− has emerged as a strong reductant, or single electron donor. Here we present techniques used to generate CO 2 ●− and we discuss applications to degrading pollutants such as halogenated alkanes. The potential occurrence of such reductions in water and aqueous aerosols is discussed, notably for the degradation of perfluoroalkyl substances. In the laboratory, CO 2 ●− is directly generated by either direct electrochemical reduction of CO 2 or hydrogen atom transfer of either formate salts with and without catalysts or ferrioxalate through photochemical or radiolytic processes. The CO 2 ●− has an ultraviolet spectrum, and CO 2 ●− vibration modes are characterized by fast kinetics using infrared and Raman spectroscopy. The second-order rate constants of the reactions of CO 2 ●− with halogenated alkanes, of -1.84 ± 0.22 V, are generally slower than that of the hydrated electron, of -2.87 V, and give a negative linear relationship with energy of lower unoccupied molecular orbital, suggesting single electron transfer mechanism in reducing the halogenated compounds.

A rapid and robust translational model for testicular aging research - N. Schmid; Y. Stepanov; M. Offner; L. Scholz; C. Herrmann; S. Petkov; R. Behr; J. B. Stöckl; T. Fröhlich; A. Mayerhofer (Histochemistry and Cell Biology, 2026)
In humans, testicular peritubular cells (TPCs) form a small compartment surrounding the seminiferous tubules and, as shown previously, undergo age-related changes. How they may contribute to the age-associated decline of testicular functions is not well known. Likewise, the mechanisms of testicular aging in humans are not well examined. This is in part due to the lack of appropriate cellular models. We aimed to establish an aging model of TPCs, which is based on immortalized nonhuman primate (NHP) peritubular cells (iMKTPCs) from Callithrix jacchus . As shown previously by a comprehensive proteomic approach, they strongly resemble human TPCs but lack the human cell-intrinsic heterogeneity. Cellular senescence was robustly induced within 10 days upon exposure to 25 µg/mL bleomycin for 24 h. This resulted in increased β-galactosidase activity, enlarged cells, and elevated transcript levels of senescence-associated secretory phenotype (SASP) molecules ( IL1b , TNFa , CCL2 ). The ability to contract upon a stimulus was reduced, as shown in live cell imaging studies. Reduced proliferation among others was indicated by a decreased abundance of proliferating cell nuclear antigen (PCNA), evident in a proteomic analysis, which also revealed massive changes (341 significantly increased and 372 decreased proteins). Bioinformatics analysis indicated a marked reduction in several cell-motility–associated proteins, whereas proteins linked to extracellular exosomes, the cytoskeleton, and lysosomal pathways were increased in abundance. To conclude, bleomycin treatment causes a rapid and robust induction of cellular senescence in a translational testicular cell model of peritubular cells. This model will enable future studies aiming to explore mechanisms and consequences of testicular aging.

Pre- and post-harvest spectral estimation of carnosic acid and rosmarinic acid in rosemary - A. Mishra; A. Krief; M.M. Sahoo; A. Schachter; I. Gonda; N. Dudai; T. Trigano; I. Herrmann (Computers and Electronics in Agriculture, 2026)

Harnessing Sentinel-2 imagery and AgERA5 data using Google Earth Engine for developing chickpea mechanistic growth modeling and pre-harvest empirical yield forecast - Omer Perach; Roy Sadeh; Asaf Avneri; Neta Solomon; David J. Bonfil; Or Ram; Harel Greenblatt; Ran N. Lati; Ittai Herrmann (Precision Agriculture, 2025)
Precision Agriculture (PA) adoption by farmers is limited by costs and technological complexity. Google Earth Engine (GEE) is used in large-scale crop research but remains underutilized for PA applications. Crop yield variability is widely studied, yet research advancements increasingly widen the gap to practical use. To address this, a GEE platform was established, harnessing Sentinel-2 and AgERA5 for chickpea mechanistic daily simulation of the Total Above-Ground Dry Biomass (TAGDB) and Grain Dry Biomass (GDB). In addition, Sentinel-2 spectral reflectance was used to train an empirical Random Forest (RF) model on GEE to forecast Grain Yield (GY) two months prior to harvest. Both mechanistic and empirical models were evaluated at field scale using GY data from 68 fields (2021–2024), including sub-field evaluation from eight fields. The mechanistic and empirical RF models achieved sub-field GY performance with a coefficient of determination (R²), root mean square error (RMSE), and relative RMSE of 0.49, 1.49 t ha⁻¹, and 19.89%, and 0.24, 1.15 t ha⁻¹, and 15.35%, respectively. At the field scale, the mechanistic model resulted in 0.43, 0.9 t ha⁻¹, and 19.35%, while the RF model achieved 0.37, 0.83 t ha⁻¹, and 17.85%, respectively. The models performed similarly to studies in other crops but with a key advantage - they can be fully executed within GEE. A companion app was built to support both the mechanistic and empirical models within GEE. Chickpea farmers can use the mechanistic model to examine the spatial progression of TAGDB and GDB, both retrospectively and in a near real time manner. The RF forecast model can then be used to anticipate GY variability prior to harvest. The streamlined design of the mechanistic model, together with the empirical model implemented in GEE and the open-source scripts available on GitHub, supports efficient adaptation to additional crops.

Toluene photo-oxidation and secondary organic aerosol formation: EUROCHAMP-2020 multi-chamber experiments - Petro Uruci; Kalliopi Florou; Marco Paglione; Christos Kaltsonoudis; Bénédicte Picquet-Varrault; Jean-François Doussin; Mathieu Cazaunau; Ari Leskinen; Liqing Hao; Annele Virtanen; David M. Bell; Anke Mutzel; et al. (Journal of Atmospheric Chemistry, 2025)

Age and body mass index are associated with dorsolateral prefrontal cortex activation in response to unhealthy food cues - Floor van Meer; Laura N. van der Laan; Gabriele Eiben; Lauren Lissner; Maike Wolters; Stefan Rach; Manfred Herrmann; Peter Erhard; Denes Molnar; Gergely Orsi; Roger A.H. Adan; Paul A.M. Smeets (Appetite, 2025)

Estimating size selectivity of Calanus spp. in plankton trawls: effect of mesh size for commercial fishery - Enis N. Kostak; Bent Herrmann; Eduardo Grimaldo; Jesse Brinkhof (Reviews in Fish Biology and Fisheries, 2025)
Calanus spp. are marine zooplankton that are considered as a potential source for aquaculture feed, due to their high abundance in the North Atlantic. The diminutive size (< 5 mm) of these zooplankton necessitates the use of fine-meshed trawls to harvest them efficiently. However, the use of fine-meshed trawls leads to high drag and thus energy demand to tow the trawl. Therefore, it is of importance to know the effect of mesh size on the capture efficiency of Calanus, and specifically to quantify which sizes of those that can be harvested effectively depending on mesh size in the trawl. Therefore, experimental trawl fishing targeting Calanus was conducted testing gears differing in mesh size to estimate their size selectivity. We used an image and artificial intelligence-based specially built and trained acquisition method to rapidly measure the size of large numbers of Calanus to prepare the catch data for size selectivity analysis . The results demonstrate a clear size selection process of Calanus in nets with mesh sizes considered for this fishery . Specifically, the size selectivity would result in a loss of 10%, 45% and 99% of Calanus if the trawl has a mesh size of 500, 750 and 1000 μm, respectively.

Size selectivity of Muller’s pearlside (Maurolicus muelleri), glacier lanternfish (Benthosema glaciale) and krill in trawls targeting the mesopelagic fish - Enis N. Kostak; Bent Herrmann; Eduardo Grimaldo; Jesse Brinkhof (Fisheries Research, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Trade-off between drag and catch performance when designing zooplankton trawls - Enis N. Kostak; Eduardo Grimaldo; Jesse Brinkhof; Bent Herrmann (Ocean Engineering, 2024)

Are rigid sorting devices necessary to control size selectivity in demersal trawl fisheries? - Bent Herrmann; Zita Bak-Jensen; Manu Sistiaga; Jesse Brinkhof; Roger B. Larsen; Eduardo Grimaldo; Kristine Cerbule; Enis N. Kostak; Morteza Eighani (Regional Studies in Marine Science, 2024)

Correction to: Chickpea leaf water potential estimation from ground and VENµS satellite - Roy Sadeh; Asaf Avneri; Yaniv Tubul; Ran N. Lati; David J. Bonfil; Zvi Peleg; Ittai Herrmann (Precision Agriculture, 2024)

Chickpea leaf water potential estimation from ground and VENµS satellite - Roy Sadeh; Asaf Avneri; Yaniv Tubul; Ran N. Lati; David J. Bonfil; Zvi Peleg; Ittai Herrmann (Precision Agriculture, 2024)

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

Optimization of chickpea irrigation in a semi-arid climate based on morpho-physiological parameters - Asaf Avneri; Zvi Peleg; David J. Bonfil; Roy Sadeh; Omer Perach; Ittai Herrmann; Shahal Abbo; Ran N. Lati (European Journal of Agronomy, 2024)

Understanding the effect of design parameters on the filtration efficiency of trawls intended for commercial harvesting of zooplankton - Eduardo Grimaldo; Bent Herrmann; Enis N. Kostak; Jesse Brinkhof (Ocean Engineering, 2023)

Bioeconomic analysis of harvesting within a predator–prey system: A case study in the Chesapeake Bay fisheries - Iordanka N. Panayotova; John Herrmann; Nathan Kolling (Ecological Modelling, 2023)

Influence of soil geomorphic factors on vegetation patterns in a model white sands ecosystem complex - Melissa A. Atwell; Mark N. Wuddivira; Sabine Fiedler; Mike Oatham; Ludger Herrmann; Bjoern Glasner; Vanessa Vetter; Hermann F. Jungkunst (CATENA, 2023)

Simulation of steam/air leakage through small-scale cracked concrete specimen - L. Bahr; J. Sievers; M. Zemann; N. Herrmann (European Journal of Environmental and Civil Engineering, 2022)

Long-Term Impacts of Invasive Insects and Pathogens on Composition, Biomass, and Diversity of Forests in Virginia’s Blue Ridge Mountains - Kristina J. Anderson-Teixeira; Valentine Herrmann; Wendy B. Cass; Alan B. Williams; Stephen J. Paull; Erika B. Gonzalez-Akre; Ryan Helcoski; Alan J. Tepley; Norman A. Bourg; Christopher T. Cosma; Abigail E. Ferson; Caroline Kittle; et al. (Ecosystems, 2021)

From empirical to theoretical models of light response curves - linking photosynthetic and metabolic acclimation - Helena A. Herrmann; Jean-Marc Schwartz; Giles N. Johnson (Photosynthesis Research, 2020)
Light response curves (LRCs) describe how the rate of photosynthesis varies as a function of light. They provide information on the maximum photosynthetic capacity, quantum yield, light compensation point and leaf radiation use efficiency of leaves. Light response curves are widely used to capture photosynthetic phenotypes in response to changing environmental conditions. However, models describing these are predominantly empirical and do not attempt to explain behaviour at a mechanistic level. Here, we use modelling to understand the metabolic changes required for photosynthetic acclimation to changing environmental conditions. Using a simple kinetic model, we predicted LRCs across the physiological temperature range of Arabidopsis thaliana and confirm these using experimental data. We use our validated metabolic model to make novel predictions about the metabolic changes of temperature acclimation. We demonstrate that NADPH utilization are enhanced in warm-acclimated plants, whereas both NADPH and CO 2 utilization is enhanced in cold-acclimated plants. We demonstrate how different metabolic acclimation strategies may lead to the same photosynthetic response across environmental change. We further identify that certain metabolic acclimation strategies, such as NADPH utilization, are only triggered when plants are moved beyond a threshold high or low temperature.

Seasonal and Interannual Variability in Net Ecosystem Production of a Subtropical Coastal Lagoon Inferred from Monthly Oxygen Surveys - Lauren E. Seidensticker; Raymond G. Najjar; Maria Herrmann; Joseph N. Boyer; Henry O. Briceño; W. Michael Kemp; Daniel J. Tomaso (Estuaries and Coasts, 2019)

Prolonged suppressive antibiotic therapy for prosthetic joint infection in the elderly: a national multicentre cohort study - V. Prendki; T. Ferry; P. Sergent; E. Oziol; E. Forestier; T. Fraisse; S. Tounes; S. Ansart; J. Gaillat; S. Bayle; O. Ruyer; F. Borlot; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Photocatalytic abatement results from a model street canyon - M. Gallus; R. Ciuraru; F. Mothes; V. Akylas; F. Barmpas; A. Beeldens; F. Bernard; E. Boonen; A. Boréave; M. Cazaunau; N. Charbonnel; H. Chen; et al. (Environmental Science and Pollution Research, 2015)

HIV neuropathy: an in vivo confocal microscopic study - Jorge L. Almodovar; Giovanni Schifitto; Michael P. McDermott; Michele Ferguson; David N. Herrmann (Journal of NeuroVirology, 2012)

H-D exchange on graphite–potassium intercalation compounds - Siegbert Rummel; Michael Herrmann; Manfred Wahren; Safar M. Yunusov; Margarita A. Ilatovskaya; Yuri B. Isaev; N. D. Lapkina; Yuri N. Novikov; Vladimir B. Shur (Isotopes in Environmental and Health Studies, 2012)

Response of a Coupled Ocean–Atmosphere Model to Greenland Ice Melting - D. Stammer; N. Agarwal; P. Herrmann; A. Köhl; C. R. Mechoso (Surveys in Geophysics, 2011)

Seasonal characteristics of tropical marine boundary layer air measured at the Cape Verde Atmospheric Observatory - L. J. Carpenter; Z. L. Fleming; K. A. Read; J. D. Lee; S. J. Moller; J. R. Hopkins; R. M. Purvis; A. C. Lewis; K. Müller; B. Heinold; H. Herrmann; K. Wadinga Fomba; et al. (Journal of Atmospheric Chemistry, 2010)

Tracking genes of ecological relevance using a genome scan in two independent regional population samples of Arabis alpina - BÉNÉDICTE N. PONCET; DORIS HERRMANN; FELIX GUGERLI; PIERRE TABERLET; ROLF HOLDEREGGER; LUDOVIC GIELLY; DELPHINE RIOUX; WILFRIED THUILLER; SERGE AUBERT; STÉPHANIE MANEL (Molecular Ecology, 2010)

Ovine progressive pneumonia provirus levels associate with breed and Ovar-DRB1 - Lynn M. Herrmann-Hoesing; Stephen N. White; Michelle R. Mousel; Gregory S. Lewis; Donald P. Knowles (Immunogenetics, 2008)

Symmetries, non-Euclidean metrics, and patterns in a Swift–Hohenberg model of the visual cortex - N. Michael Mayer; Matthew Browne; J. Michael Herrmann; Minoru Asada (Biological Cybernetics, 2008)

Genomic analysis of Ovis aries (Ovar) MHC class IIa loci - Lynn M. Herrmann-Hoesing; Stephen N. White; Lowell S. Kappmeyer; David R. Herndon; Donald P. Knowles (Immunogenetics, 2008)

Induction of apoptosis by spermine-metabolites in primary human blood cells and various tumor cell lines - M. Schiller; N. Blank; P. Heyder; M. Herrmann; U. S. Gaipl; J. R. Kalden; H. M. Lorenz (Apoptosis, 2005)

Treatment of Severe Candida Infections in High-Risk Patients in Germany: Consensus Formed by a Panel of Interdisciplinary Investigators - Büchner T.; Fegeler W.; Bernhardt H.; Brockmeyer N.; Duswald K.-H.; Herrmann M.; Heuser D.; Jehn U.; Just-Nübling G.; Karthaus M.; Maschmeyer G.; Müller F.-M.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Human astrovirus isolation and propagation in multiple cell lines - J. P. Brinker; N. R. Blacklow; J. E. Herrmann (Archives of Virology, 2000)

Diurnal changes in xylem pressure and mesophyll cell turgor pressure of the lianaTetrastigma voinierianum: The role of cell turgor in long-distance water transport - F. Thrmer; J. J. Zhu; N. Gierlinger; H. Schneider; R. Benkert; P. Gener; B. Herrmann; F. -W. Bentrup; U. Zimmerniann (Protoplasma, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Effect of dimethicone (polysilane gel) on the stereoselective pharmacokinetics of ketoprofen - N. Presle; F. Lapicque; P. Gillet; M.-A. Herrmann; B. Bannwarth; P. Netter (European Journal of Clinical Pharmacology, 1998)

Plant regeneration from leaf protoplasts of evening primrose ( Oenothera hookeri ) - N. Kuchuk; R. G. Herrmann; H.-U. Koop (Plant Cell Reports, 1998)

Book Reviews - B. Herrmann; B. Schweitzer; N. Biedinger (The Science of Nature, 1998)

Immunological characterization of the Marin County strain of astrovirus - J. E. Herrmann; W. D. Cubitt; R. W. Hudson; Dorothy M. Perron-Henry; L. S. Oshiro; N. R. Blacklow (Archives of Virology, 1990)

Plaque quantitation and virus neutralization assays for human astroviruses - R. W. Hudson; J. E. Herrmann; N. R. Blacklow (Archives of Virology, 1989)

Preparation and characterization of monoclonal antibodies to enteric adenovirus types 40 and 41 - J. E. Herrmann; Dorothy M. Perron-Henry; Darlene Stobbs-Walro; N. R. Blacklow (Archives of Virology, 1987)